Strategic maneuvering for political change a pragma-dialectical analysis of Egyptian anti-regime columns - Omar, Ahmed Abdulhameed (Argumentation in context ;, 2019)
In Strategic Maneuvering for Political Change, the author analyzes five political columns written before 2011 by Al Aswany, a prominent Egyptian novelist, using the lens of the extended pragma-dialectical theory of argumentation. What these texts have in common is the use of narrative, fictional and semi-literary techniques to strategically maneuver in supporting the feasibility of political change. It is a contribution to explain how an anti-regime writer paved the way to the Arab Spring in Egypt, and thus goes against a common opinion that the Arab Spring in Egypt was fortuitous or a wholly social-media-based movement. This monograph is an attempt to help argumentation theorists, linguists, analysts of narratives, and political scientists better understand and evaluate how fiction and narration can be effective means of persuasion in the domain of political communication. It therefore reconsiders the non-straightforward and artistic variants of the language of politics.